(untitled) (Baghdad Science Journal, 2006)
Took apple branches Genuine and Architecture tissue cultured in vitro 3 cm long and planted in the middle of food MS that contains different concentrations of inorganic salts and of Mntmat free growth and incubated Transplanter to study their effect on rooting Aalavra